ANALYSIS OF CUSTOMER EXPERIENCE QUALITY AT VEREL BAKERY & COFFEE SHOP MANADO - Tandaju, Frederik J.; Saerang, David P.E.; Tielung, Maria V.J. (FEB Universitas Sam Ratulangi Manado, 2019)
Abstract: Customer experience is the product of an interaction between an organization and a customer over the duration of their relationship. Customer experience means that the individualâ€™s experience during all points of contact matches the individualâ€™s expectations. The aim of this research to know how is the customer experience quality at Verel Bakery & Coffee Shop. To achieve these objectives the researcher got information from 10 informants using qualitative study which is in-depth interview. Meanwhile, in-depth interview is used to collect the data among the respondents which are Verel Bakery & Coffee Shop Manado customers. From the results, many of the respondents give a positive review but few of them give a negative review about Verel Bakery & Coffee Shop Manado. Some recommendations proposed for the customer, it is good to know about the customer experience because they need to understand what factors make them experience. For Verel Bakery & Coffee Shop Manado, this research may be useful in order to decrease the bad experience from customers and to improve Verel Bakery & Coffee Shop performances.Â Keywords: customer experience quality, verel bakery & coffee shop